2018
DOI: 10.1093/jhered/esy037
|View full text |Cite
|
Sign up to set email alerts
|

Colonizing the Wild West: Low Diversity of Complete Mitochondrial Genomes in Western North Pacific Killer Whales Suggests a Founder Effect

Abstract: In the North Pacific, fish-eating R-type "resident" and mammal-eating T-type "transient" killer whales do not interbreed and differ in ecology and behavior. Full-length mitochondrial genomes (about 16.4 kbp) were sequenced and assembled for 12 R-type and 14 T-type killer whale samples from different areas of the western North Pacific. All R-type individuals had the same haplotype, previously described for R-type killer whales from both eastern and western North Pacific. However, haplotype diversity of R-type k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 34 publications
2
9
0
Order By: Relevance
“…The demographic contraction and subsequent expansion observed in the coastal populations of this study, as well as the significantly reduced nucleotide and haplotype diversities, suggest that bottlenose dolphins indeed expanded their range northwards to coastal areas via founder events during leading-edge expansion. A similar founder event has recently been suggested to give rise to the present-day resident-type killer whale communities in the Russian Pacific (Filatova et al, 2018), and rapid demographic expansions after the LGM have been documented across other marine taxa (e.g. Klimova et al, 2014;Jenkins et al, 2018).…”
Section: Discussionsupporting
confidence: 53%
“…The demographic contraction and subsequent expansion observed in the coastal populations of this study, as well as the significantly reduced nucleotide and haplotype diversities, suggest that bottlenose dolphins indeed expanded their range northwards to coastal areas via founder events during leading-edge expansion. A similar founder event has recently been suggested to give rise to the present-day resident-type killer whale communities in the Russian Pacific (Filatova et al, 2018), and rapid demographic expansions after the LGM have been documented across other marine taxa (e.g. Klimova et al, 2014;Jenkins et al, 2018).…”
Section: Discussionsupporting
confidence: 53%
“…During periods of ice formation, killer whales may have responded by retreating east to the Aleutian Islands that remained ice-free, or south to Japan. Results of complete mitogenome sequencing in Morin et al (2015) and Filatova et al (2018) support the hypothesis of the central Aleutian refugium.…”
Section: Discussionsupporting
confidence: 61%
“…This unusually low haplotype diversity encouraged the further analysis of complete mitochondrial DNA (Morin et al, 2010, 2015), which revealed higher diversity in the Aleutian Islands than off the mainland. Filatova et al (2018) showed that all R‐type killer whales in the western North Pacific from the northern Kuril Islands to Karaginsky Gulf, a distance of 1,100 km, shared the same complete mtDNA haplotype, which is unusual for animal populations. Mitogenome diversity was slightly greater in the eastern North Pacific (3 complete mitogenome haplotypes), and the greatest diversity (11 complete mitogenome haplotypes) was observed in the central Aleutian Islands.…”
Section: Introductionmentioning
confidence: 99%
“…Our “resident” samples originate from across the ecotype's North Pacific range, from Washington State, USA to the Sea of Okhotsk off Eastern Russia. Therefore, the variation segregating in the “resident” ecotype and driving PC2 in Figure b must predate the separation into the several “resident” subpopulations which have subsequently colonised much of the Pacific rim (Filatova et al, ). If this drift in allele frequencies shared among “residents” occurred postadmixture with the “transient” ecotype, it would increase genetic differentiation between the two currently sympatric North Pacific ecotypes.…”
Section: Discussionmentioning
confidence: 99%